A CRITICAL DISCOURSE ANALYSIS OF PAKISTAN'S HIGHER EDUCATION COMMISSION LANGUAGE POLICY FRAMEWORK: AN ARCHITECTURE OF LINGUISTIC CONTROL (Contemporary Journal of Social Science Review, 2025)
This critical discourse analysis examines the language policy structure of the Higher Education Commission (HEC) in Pakistan with an aim of explaining how discourse has been used to construct power of an institution in a post-colonial situation. Through an integrated theoretical approach that explores the official documents between 2014 and 2023, the study argues that the policy is an apparatus of linguistic governance, but not an administrative device that is neutral. It exposes a multi-layered discursive regime that naturalises English hegemony through the grammatical requirements, interdiscursively combines the neoliberal and developmental ideologies, and uses ideological tactics that generate acquiescence at the expense of the local languages. The analysis shows the policy constitutes a kind of governmentality, creating subjectivities of failed students and submissive professors, naturalizing English as lingo capital, and arranging an epistemic shift to the knowledge of the Anglophone. The study thus throws light on the process of discursive politics of power within the post-colonial education that has ramifications of equity, identity and epistemic justice.